Peran Pendampingan dan Pembinaan Badan Usaha Milik Desa sebagai Penggerak Ekonomi dalam Meningkatkan Kesejahteraan Masyarakat Di Desa Onozalukhu - Zalukhu, Chindy Martha Ledy; Hulu, Syukur Kasieli; Harefa, Amstrong; Harefa, Hendrikus O. N. (Innovative: Journal Of Social Science Research, 2024)
The role of Mentoring and Development of Village-Owned Enterprises is an effort to provide support, guidance and training to BUMDes in order to increase their capacity, performance and contribution in developing the village economy which involves interaction between the government and village communities in improving the economy in Onozalukhu village. This research uses a qualitative method using a descriptive approach. The research instrument is the researcher himself. Data collection techniques use interviews, observation and documentation. The results of the research and discussion concluded that BUMDes have a very important role in encouraging village economic growth and improving community welfare. Mentoring and coaching can help BUMDes improve management, strengthen community participation, and overcome various difficulties faced. The role of a village head is to fully support existing programs in the village by monitoring every activity carried out in BUMDes so that they can run well.